If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -1) + 6x = 33 Reorder the terms: 3(-1 + 2x) + 6x = 33 (-1 * 3 + 2x * 3) + 6x = 33 (-3 + 6x) + 6x = 33 Combine like terms: 6x + 6x = 12x -3 + 12x = 33 Solving -3 + 12x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 12x = 33 + 3 Combine like terms: -3 + 3 = 0 0 + 12x = 33 + 3 12x = 33 + 3 Combine like terms: 33 + 3 = 36 12x = 36 Divide each side by '12'. x = 3 Simplifying x = 3
| 16p^4-88p^3+121p^2=0 | | 25-x=x^2 | | 64+9x=104+4x | | 7y+126=9x | | 25=x^2+x | | 6+4(-10)+7(-10)=3(6(-10)-12)-4(-10-6) | | (x+4)(x-6)=432 | | 27y-1=0 | | 8x+3=31-5x | | (x+4)(x-6)=216 | | 39-x=36-10x | | z^7+2z^4+z=0 | | 57x+23-42x=-145 | | 2x+13=-15-5x | | 2x^2-22x+59=0 | | 1-2a-(3a-10)=(3-a) | | 0.75x^2+1.23x-2.48=0 | | x+3=105 | | 9m-5=3m+37 | | 2x+5y=9200 | | 10x+22x-5=8(4+7) | | X(x+40)=3(x+45) | | 64-729x^9=0 | | 2x(2+2)=16 | | 2x(2+2)=14 | | 2x(2+2)=12 | | 10h-17=53 | | 39-3x=36-10x | | 14k+4.5=k+14 | | 2+8x=16+x | | 3x-10+2=45 | | 75-n=50 |